Anesthesia and the neurobiology of fear and posttraumatic stress disorder. Issue 5 (19th October 2022) - Vogt, Keith M.; Pryor, Kane O.
Abstract : Purpose of review: Dysfunction of fear memory systems underlie a cluster of clinically important and highly prevalent psychological morbidities seen in perioperative and critical care patients, most archetypally posttraumatic stress disorder (PTSD). Several sedative-hypnotics and analgesics are known to modulate fear systems, and it is theoretically plausible that clinical decisions of the anesthesiologist could impact psychological outcomes. This review aims to provide a focused synthesis of relevant literature from multiple fields of research. Recent findings: There is evidence in some contexts that unconscious fear memory systems are less sensitive to anesthetics than are conscious memory systems. Opiates may suppress the activation of fear systems and have benefit in the prevention of PTSD following trauma. There is inconsistent evidence that the use of propofol and benzodiazepines for sedation following trauma may potentiate the development of PTSD relative to other drugs. The benefits of ketamine seen in the treatment of major depression are not clearly replicated in PTSD-cluster psychopathologies, and its effects on fear processes are complex. Summary: There are multiple theoretical mechanisms by which anesthetic drugs can modulate fear systems and clinically important fear-based psychopathologies. The current state of research provides some evidence to support further hypothesis investigation. However, the absence of effectiveness studies and the inconsistent signals from smaller studies provide insufficient evidence to currently offer firm clinical guidance.